Constraints In Preparing Consolidated Financial Statements Between The Algerian Fas And Ifrs - Djafri Omar (جامعة الوادي University Of Eloued, 2024)
The main objective of this article is to focus on the problem of the application of the Financial Accounting System (FAS), largely inspired by the "International Accounting Standards" IAS-IFRS in terms of accounting consolidation. Expecting a documentary analytical approach, the study concluded that Algerian groups of companies find a lot of difficulties when drawing up their financial statements, not only with regard to accounting principles, but also with regard to tax laws. These constraints are due to the lack of updates of the SCF by the National Accounting Council, which is supposed to be the national standard setter, as well as to the accounting culture of financial statement preparers who are called upon to communicate reliable and comparable information to their users, in particular, the shareholders in order to protect their interests
Keywords: Accounting Consolidation; Accounting Standards; Financial Accounting System (FAS); Shareholder Interests; Tax legislation